Comparative Stiffness of an Equine Distal Sesamoid Bone Fracture Model Stabilized with 3.5-mm versus 4.5-mm Cortical Bone Screws in Lag Fashion - Mampe, Jessica R.; Tatarniuk, Dane M.; Suarez-Fuentes, David G.; Kraus, Karl H. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to to determine the comparative stiffness following repair of an axial sagittal fracture model in equine distal sesamoid bones using either a single 3.5-mm or 4.5-mm cortical bone screw placed in lag fashion.Study Design The present study was an in vitro biomechanical study.Results The mean (±standard deviation) stiffness value for the 4.5-mm screw–bone construct (522.49 N/mm ± 168.21) was significantly greater than the 3.5-mm screw-bone construct (408.46 N/mm ± 131.13) (p = 0.047). This represents a 28% difference in mean stiffness.Conclusions In vitro, the 4.5-mm screw–bone construct creates a stiffer repair of fractured distal sesamoid bones by a margin of 28%. The 4.5-mm cortical bone screw may better withstand forces imparted on the distal sesamoid bone sustained during anaesthetic recovery, normal weight bearing and athletic exercise, thereby minimizing the risk of implant failure.
Keywords: distal sesamoid bone; lag screw fixation; four-point bending; cortical bone screw; equine